2022
DOI: 10.1155/2022/9991855
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Angle of the Guide Plate and Crushing Performance in Vertical Shaft Crushers

Abstract: A geometric model of rotors is established on the basis of the structure of vertical shaft impact crusher. The dynamic simulation of the rotor is carried out by using the discrete element software EDEM. At the same time, the correlation between the angle of the guide plate and the crushing performance of the crusher is studied systematically. The optimal angle of the guide plate is obtained by theoretical analysis of the particle motion. The simulation method is used to analyze the velocity of particles, so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In [64], on the basis of the method of discrete elements, a rotor of an impact crusher with a vertical shaft was modeled. The effect of various guide plate angles on the rotor acceleration characteristics was studied by extracting particle velocity data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [64], on the basis of the method of discrete elements, a rotor of an impact crusher with a vertical shaft was modeled. The effect of various guide plate angles on the rotor acceleration characteristics was studied by extracting particle velocity data.…”
Section: Resultsmentioning
confidence: 99%
“…Geometric model of rotors based on the design of an impact crusher with a vertical shaft [64] Impact crusher front guide plate wear is the most serious At the angle of the crusher guide plate, the maximum peak particle velocity in the whole process was relatively high 8 Physical and mathematical model for designing and testing the annular armor of a vertical shaft impact crusher [65] The angle of impact between the particles of the original material and the segment of the annular armor in most cases is not determined…”
Section: Disadvantages Of the Mathematical Modelmentioning
confidence: 99%
“…The results indicated that the rotor with six channels exhibited the most reasonable structure, offering optimal acceleration effects and crushing efficiency. Feng [20] utilized discrete element simulation software to dynamically simulate the rotor, analyzing particle velocity. The study focused on understanding the influence of the guide plate angle on particle acceleration effects.…”
Section: Introductionmentioning
confidence: 99%